Circadian Rhythms and Clock Genes in Reproduction: Insights From Behavior and the Female Rabbit’s Brain - Caba, Mario; González-Mariscal, Gabriela; Meza, Enrique (Frontiers in Endocrinology, 2018)
Clock gene oscillations are necessary for a successful pregnancy and parturition, but little is known about their function during lactation, a period demanding from the mother multiple physiological and behavioral adaptations to fulfill the requirements of the offspring. First we will focus on circadian rhythms and clock genes in reproductive tissues mainly in rodents. Disruption of circadian rhythms or proper rhythmic oscillations of clock genes provoke reproductive problems, as found in clock gene knockout mice. Then we will focus mainly on the rabbit doe as this mammal nurses the young just once a day with circadian periodicity. This daily event synchronizes behavior and the activity of specific brain regions critical for reproductive neuroendocrinology and maternal behavior, like the preoptic area. This region shows strong rhythms of the PER1 protein (product of the Per1 clock gene) associated with circadian nursing. Additionally, neuroendocrine cells related to milk production and ejection are also synchronized to daily nursing. A threshold of suckling is necessary to entrain once a day nursing; this process is independent of milk output as even virgin does (behaving maternally following anosmia) can display circadian nursing behavior. A timing motivational mechanism may regulate such behavior as mesolimbic dopaminergic cells are entrained by daily nursing. Finally we will explore about the clinical importance of circadian rhythms. Indeed, women in chronic shift-work schedules show problems in their menstrual cycles and pregnancies and also have a high risk of preterm delivery, making this an important field of translational research.